The effective responses of a tourism and gaming city towards the devastating effects of pandemic: a case study of Macao. Issue 2 (15th February 2021) - Im, Ut Lon; Lam, Ching-Chi Cindia; Ma, Erdan
Abstract : Purpose: COVID-19 has hard-hit the global economy when the majority of developed countries could not demonstrate effective resolutions even a year after the outbreak. This study aims to present how government or policymakers could minimize the negative impacts of major incidents (pandemic) and speed up the process of recovery. It was also intended to identify effective strategies for crisis management. Design/methodology/approach: A mixed research method was applied. Qualitative research studies of interviews were used to collect primary data from the stakeholders while archival research method of textual and documental information was used for secondary data on the pandemic facts. Findings: The impacts of the governmental and enterprise actions with a focus on effective mega-crisis management strategies were structured based on the three themes, namely, appropriate measures, timely decisions and the role of the government. These strategies can minimize the destruction to the economy (or organization) while stabilize the emotional and psychological aspects of the people during the crisis and lead the society back on track once the crisis starts to diminish. Originality/value: The experience of Macao in successfully responding to the crisis of pandemic provides constructive references to policymakers on the set up of timely strategic plans and business management on remedy actions, particularly to regions where the pandemic is still out of control.